A construção discursiva da argumentação em sala de aula: uma proposta de jogo digital como ferramenta de ensino-aprendizagem - Daniela Cristina Sales (2016)
This research deals with the argument, from an interactional and discursive perspective, as a teaching object in Portuguese classes. Man is a social being who acts through language in different social spheres, according to objectives, intentions and need to reach the other a certain reaction. The argument, in this view, is a dialogical phenomenon (FIORIN, 2015). The proposal of this work arises from the need to think of new alternatives and pedagogical practices that can contribute to the formation of argumentative competence of students of the final stage (9th grade) of elementary school. Digital technologies have provided new opportunities for reading and writing, turning social interactions and ways of life. Teenagers live immersed in cyberspace, being seduced by the various features and applications available in the virtual environment, especially for digital games. Considering this context, the central objective of this research is to develop the pedagogical design of a digital learning object type game for teaching argumentative strategies. Educational digital games, as several studies show, can bring many benefits to the teaching-learning process. In addition to the digital game, we developed a teaching module consists of reading workshops, understanding and text production, focusing on the discursive genre opinion article. The educational goal is, through the activities that make up the game and teaching modules, consolidate basic skills needed to argue, persuasively, to win the conviction and guide ways of thinking, seeing and feeling the other (AMOSSY, 2007/2011). This teaching proposal is intended to provide students with playful experiences, dynamic, meaningful and, above all, facilitating learning. The questions that guide this work are: What argumentative strategies for writing production, would be more appropriate to be taught to students in 9th grade of elementary school? It would be possible and feasible to develop an educational digital game for teaching argumentative strategies? The methodology is qualitative, with a view to intervention. The corpus of the research consists of a didactic module and an educational digital game. The theoretical framework is based on the studies of argument Chaim Perelman and Olbrechts-Tyteca (2005); Ruth Amossy (2000/2006/2011), whose purpose is to articulate rhetoric, the New Rhetoric and Discourse Analysis; Koch (1984/1996/2000), Abreu (2009); Fiorin (2014/2015) among others.